Chance: A Tale in Two Parts - Conrad, Joseph, 1857-1924 (Salt Lake City, UT : Project Gutenberg, 1998)
"Chance: A Tale in Two Parts" by Joseph Conrad is a novel published in 1913. Narrated through multiple voices, including Conrad's recurring character Charles Marlow, the story follows Flora de Barral, daughter of a convicted swindler. Her sheltered existence collapses with her father's imprisonment, forcing her to depend on others' uncertain generosity until she escapes through marriage to Captain Anthony. The novel explores their enigmatic union through fragmented perspectives, building toward a climactic resolution when her father rejoins them at sea. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Chance_(Conrad_novel)
Release date is 1998-09-01
David Price
Keywords: Sea stories; Psychological fiction; Young women -- Fiction; Love stories; Fathers and daughters -- Fiction; Children of prisoners -- Fiction; Ship captains' spouses -- Fiction